Properties of Knee Joint Position Sense Tests for Anterior Cruciate Ligament Injury: A Systematic Review and Meta-analysis. Issue 8 (20th August 2021) - Strong, Andrew; Arumugam, Ashokan; Tengman, Eva; Röijezon, Ulrik; Häger, Charlotte K.
Background: Knee proprioception is believed to be deficient after anterior cruciate ligament (ACL) injury. Tests of joint position sense (JPS) are commonly used to assess knee proprioception, but their psychometric properties (PMPs) are largely unknown. Purpose: To evaluate the PMPs (reliability, validity, and responsiveness) of existing knee JPS tests targeting individuals with ACL injury. Study Design: Systematic review; Level of evidence, 4. Methods: PubMed, Allied and Complementary Medicine, CINAHL, SPORTDiscus, Web of Science, Scopus, CENTRAL, and ProQuest databases were searched to identify studies that assessed PMPs of knee JPS tests in individuals with ACL injury. The risk of bias for each included study was assessed and rated at the outcome level for each knee JPS test. Overall quality and levels of evidence for each PMP were rated according to established criteria. Meta-analyses with mean differences were conducted using random effects models when adequate data were available. Results: Included were 80 studies covering 119 versions of knee JPS tests. Meta-analyses indicated sufficient quality for known-groups and discriminative validity (ACL-injured knees vs knees of asymptomatic controls and contralateral noninjured knees, respectively), owing to significantly greater absolute errors for ACL-injured knees based on a strong level of evidence. A meta-analysis showed insufficient quality for responsiveness, which was attributed to a lack of significant change over time after diverse interventions with a moderate level of evidence. Statistical heterogeneity ( I 2 > 40%) was evident in the majority of meta-analyses. All remaining PMPs (reliability, measurement error, criterion validity, convergent validity, and other PMPs related to responsiveness) were assessed qualitatively, and they failed to achieve a sufficient quality rating. This was a result of either the study outcomes not agreeing with the statistical cutoff values/hypotheses or the level of evidence being rated as conflicting/unknown or based on only a single study. Conclusion: Knee JPS tests appear to have sufficient validity in differentiating ACL-injured knees from asymptomatic knees. Further evidence of high methodologic quality is required to ascertain the reliability, responsiveness, and other types of validity assessed here. We recommend investigations that compare the modifiable methodologic components of knee JPS tests on their PMPs to develop standardized evidence-based tests.